2022
DOI: 10.3390/ijms23020597
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Enhancing Effect of Submerged Culture of Ceriporia lacerata Mycelia on Cyclophosphamide-Induced Immunosuppressed Mice and the Underlying Mechanisms in Macrophages

Abstract: The white-rot fungi Ceriporia lacerata is used in bioremediation, such as lignocellulose degradation, in nature. Submerged cultures and extracts of C. lacerata mycelia (CLM) have been reported to contain various active ingredients, including β-glucan and extracellular polysaccharides, and to exert anti-diabetogenic properties in mice and cell lines. However, the immunostimulatory effects have not yet been reported. This study aimed to identify the immunomodulatory effects, and underlying mechanisms thereof, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In addition, NN exerts anti-inflammatory effects on LPS-stimulated RAW 264.7 macrophages through inhibition of NF-κB and MAPK pathways ( 44 48 ). Similar to a previous study ( 35 , 40 48 ), our results showed that KPNN increased the p-NF-κB and p-ERK in RAW 264.7 cells. These findings are thought to be because of the positive role of KPNN in activating cytokines in Th1 cells, stimulating immune factors in the body, and increasing the activity of NK cells ( 49 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, NN exerts anti-inflammatory effects on LPS-stimulated RAW 264.7 macrophages through inhibition of NF-κB and MAPK pathways ( 44 48 ). Similar to a previous study ( 35 , 40 48 ), our results showed that KPNN increased the p-NF-κB and p-ERK in RAW 264.7 cells. These findings are thought to be because of the positive role of KPNN in activating cytokines in Th1 cells, stimulating immune factors in the body, and increasing the activity of NK cells ( 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…LPS-induced activation of macrophages produces pro-inflammatory cytokines (IL-1, TNF-α, IL-6, and IFN-γ), leading to the activation of phospholipase A2, which produces lipid metabolites of arachidonic acid, such as prostaglandins, and NO. Macrophages also induce MAPK-dependent phosphorylation, thereby activating multiple transcription factors ( 32 – 35 ). LPS upregulates TNF-α and iNOS expression by activating multiple transcription factors and inducing MAPK-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations